KEPEDULIAN MASYARAKAT DALAM PENGELOLAAN SAMPAH DI PASAR HULAWA KECAMATAN TELAGA KABUPATEN GORONTALO - PanaI, Heny (Sainstek, 2010)
ABSTRACT: Garbage become a crucial problem and also effect from its stacks such as stench and become a place for disease vector, esthetically not good, and can become a major factor for flood. This research aimed to reveal how people care in garbage management. People or community in this research refer to seller, buyer, the office of Environmental Affairs, cooperative affairs, industry and commerce affairs Kabupaten Gorontalo in this case market service area, entrepreneur and markets cleaning service. Indicator of care in this research is consist of : (1) Community care in garbage management, (2) community attitude in garbage management consist of (1) planning, (2) organizing, (3) leadership, (4) control and supervising. Method used in this research is qualitative descriptive along with purposive sampling research technique, interview used snow balling sample. Data checking used (1) triangulation, (2) participation extension, (3) monitoring perseverance. This research concluded that market community care in garbage management show by : (1) Lack of attention from community in garbage management, (2) lack of attitude from community in garbage management that cause difficulties in environment healthy in this research location. Keywords : care or attention, garbage management.